Trendi v razvoju svetovnega gospodarstva v postindustrijskem obdobju - Lorber, Lučka (Geografski obzornik, 2000)
Scientific development and technological progress caused structural changes in the economy, particularly disindustrialization and transition from the secondary production to the tertiary one as well as the formation of the global market. The investments into researches and development are of primary importance for the economic development of the region and for the process of globalization
Keywords: ekonomski razvoj; globalizacija; industrializacija; industrijska družba; postindustrijska družba; svetovno gospodarstvo; tehnološki razvoj